Do women shy away from risky skill games? - Lambrecht, Marco; Oechssler, Joerg (AWI discussion paper series, 2022)
A risky skill game is a game in which skill plays an important role but outcomes are also strongly influenced by random factors. Examples are poker or blackjack but also many economic activities like trading on financial markets. In an online experiment we let subjects choose how often they want to play a risky skill game. We find that women play only half as many rounds in risky skill games if the influence of chance is large. There is no gender difference if the influence of chance is small or if outcomes depend exclusively on chance.
Keywords: Graue Literatur